Global business today - Hill, Charles W. L. (New York; McGraw Hill LLC, 2020)
"As part of the overall revision process, changes have been made to every chapter in the book. All statistics have been updated to incorporate the most recently available data. Important current events have been incorporated into the text and discussed at length"--
Includes index.
Ages 18+
PB
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: International business enterprises -- Management; International trade; Investments, Foreign; Capital market